Host shifting and host sharing in a genus of specialist flies diversifying alongside their sunflower hosts. (28th November 2020) - Hippee, Alaine C.; Beer, Marc A.; Bagley, Robin K.; Condon, Marty A.; Kitchen, Andrew; Lisowski, Edward A.; Norrbom, Allen L.; Forbes, Andrew A.
Abstract: Congeneric parasites are unlikely to specialize on the same tissues of the same host species, likely because of strong multifarious selection against niche overlap. Exceptions where >1 congeneric species use the same tissues reveal important insights into ecological factors underlying the origins and maintenance of diversity. Larvae of sunflower maggot flies in the genus Strauzia feed on plants in the family Asteraceae. Although Strauzia tend to be host specialists, some species specialize on the same hosts. To resolve the origins of host sharing among these specialist flies, we used reduced representation genomic sequencing to infer the first multilocus phylogeny of genus Strauzia . Our results show that Helianthus tuberosus and Helianthus grosseserratus each host three different Strauzia species and that the flies co‐occurring on a host are not one another's closest relatives. Though this pattern implies that host sharing is most likely the result of host shifts, these may not all be host shifts in the conventional sense of an insect moving onto an entirely new plant. Many hosts of Strauzia belong to a clade of perennial sunflowers that arose 1–2 MYA and are noted for frequent introgression and hybrid speciation events. Our divergence time estimates for all of the Helianthus ‐associated Strauzia are within this same time window (<1 MYA), suggesting that rapid and recent adaptive introgression and speciation in Helianthus may have instigated the diversification of Strauzia, with some flies converging upon a single plant host after their respective ancestral host plants hybridized to form a new sunflower species. Abstract : Phylogenetic analysis of specialist fruit flies in the genus Strauzia shows that fly species sharing the same host plant do so because of multiple host shift events. Different fly species shifting onto a shared host plant appears to have happened at least twice in the evolutionary history of Strauzia .